Avaliação de aspectos de conservação/degradação e das formas de uso do parque municipal São Francisco de Assis, no município de Assis Chateaubriand - PR - Augusto, José Renato (2011)
This work was developed in the San Francisco de Assis Park, located in the urban perimeter of Assis Chateaubriand-PR city. The study had as purpose to characterize the current situation of the Municipal Park San Francisco de Assis, by means of the identification and distribution of the native species and exotic invaders, as well as the impacts caused for the humane action, evaluating the different forms of use of this area. The phytogeographic survey was carried through identification of botanical material in parcels of 100m2, resulting in the identification of fifty one species that occurs with frequency, pertaining the twenty seven families. We can conclude that this urban park still protects a rich biodiversity. Despite denoting a fine diversity, especially in flora, it was observed pressure of invading exotic species over native species, unchaining an ecological disequilibrium. Other identified problems are the interference of human activities in different areas of the green area; there were observed compactation of the soil and ground, caused by people action and cars, inside de conservation unit; other problem is about garbage discarded in the area, especially dismissable and organic garbage. These problems reflects lack of an effective management in the area, as precarious maintenance, lack of ambient agents to guide the community; lack of sensitization of the visitors. Another study demonstrated that most of the visitors are from the central area of the city. These surveys had served to verify the main problems faced by the conservation unit, evidencing the urgency in the elaboration of a plan of handling in the Municipal Park San Francisco de Assis. The work encloses a preliminary zoning of the park, on the basis of the geographic variables studied, that can precede the elaboration of a complete plan of handling, interdisciplinary, aiming at an optimum use for the area.